2021
DOI: 10.1021/acsabm.0c01354
|View full text |Cite
|
Sign up to set email alerts
|

Nanofeature Size and Morphology of Tantalum Oxide Surfaces Control Osteoblast Functions

Abstract: Tantalum is one of the most corrosion-resistant materials and has mechanical properties that are suitable for orthopedic applications. However, tantalum exhibits bioinert characteristics and cannot promote the desired level of osseointegration with juxtaposed bone tissues. To enhance the bioactivity of tantalum, nanoscale surface modifications via anodization could be a potential approach. In this study, surface features having nanotubular, nanodimple, and nanocoral morphologies were fabricated onto tantalum b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Creating a nanostructured topography on implant surfaces is a promising strategy to improve the biological response and prevent bacterial colonization on 316L SS implant surfaces. , Anodic oxidation (anodization) is an electrochemical surface modification technique to form a nanostructured oxide layer on the surfaces of valve metals, including aluminum, , titanium, , zirconium, , etc. In the last decade, anodization of different metallic implant components received considerable attention due to it is simplicity and ability to obtain nanofeatures having different feature sizes and morphologies by changing the anodization parameters, i.e., voltage, time, etc. For instance, our research group previously created nanopores, nanodimples (NDs), nanotubes, and nanocoral morphologies on tantalum surfaces and controlled the feature size of these morphologies between 20 and 140 nm to enhance the osteoblast (bone cell) functions on these surfaces . In another study, we formed nanotubular structures on titanium surfaces via anodization and controlled the feature size of these nanotubular structures between 25 and 140 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creating a nanostructured topography on implant surfaces is a promising strategy to improve the biological response and prevent bacterial colonization on 316L SS implant surfaces. , Anodic oxidation (anodization) is an electrochemical surface modification technique to form a nanostructured oxide layer on the surfaces of valve metals, including aluminum, , titanium, , zirconium, , etc. In the last decade, anodization of different metallic implant components received considerable attention due to it is simplicity and ability to obtain nanofeatures having different feature sizes and morphologies by changing the anodization parameters, i.e., voltage, time, etc. For instance, our research group previously created nanopores, nanodimples (NDs), nanotubes, and nanocoral morphologies on tantalum surfaces and controlled the feature size of these morphologies between 20 and 140 nm to enhance the osteoblast (bone cell) functions on these surfaces . In another study, we formed nanotubular structures on titanium surfaces via anodization and controlled the feature size of these nanotubular structures between 25 and 140 nm.…”
Section: Introductionmentioning
confidence: 99%
“… 14 17 For instance, our research group previously created nanopores, nanodimples (NDs), nanotubes, and nanocoral morphologies on tantalum surfaces and controlled the feature size of these morphologies between 20 and 140 nm to enhance the osteoblast (bone cell) functions on these surfaces. 18 In another study, we formed nanotubular structures on titanium surfaces via anodization and controlled the feature size of these nanotubular structures between 25 and 140 nm. The nanotubular structures improved exosome secretion, which in turn stimulated the endothelial cell viability.…”
Section: Introductionmentioning
confidence: 99%
“…Above all, the composite efficiently facilitated the proliferation of experimental cells in this study. Some relevant literature has demonstrated that hydroxyapatite can motivate the cell proliferation of human and animal osteoblasts 44–46 . In general, it can be concluded that the composite significantly enhanced cell proliferation.…”
Section: Resultsmentioning
confidence: 98%
“…Some relevant literature has demonstrated that hydroxyapatite can motivate the cell proliferation of human and animal osteoblasts. [44][45][46] In general, it can be concluded that the composite significantly enhanced cell proliferation.…”
Section: In Vitro Cell Studymentioning
confidence: 99%
“…Finally, chemical treatments and chemical syntheses can also produce a variety of topographical features. For example, nanopore arrays can be fabricated by electrochemical anodization, [ 54b–d,77 ] micro/nanoscale roughness can be obtained by wet chemical etching, [ 53b,78 ] wire arrays can be synthesized by chemical vapor deposition, [ 55b,c,79 ] induced crystallization, [ 80 ] electrochemical polymerization [ 51b,81 ] and hydrothermal treatment. [ 55a,d,82 ] Chemical treatments and chemical syntheses are not confined to 2D surfaces, and thus hold great potential for introducing topographical features into 3D bulk and porous scaffolds.…”
Section: Delivering Mechanical Stimulation To Cellsmentioning
confidence: 99%